Effects of alkyl chain length on the cold crystallization of Schiff-base nickel(ii) complexes. Issue 33 (2nd August 2022) - Ishikawa, Toru; Honda, Akinori; Miyamura, Kazuo
Abstract : Thermal behavior including the cold crystallization of a Schiff base complex bearing two methyl groups was investigated. Additionally, the effect of alkoxy chain length was studied. Abstract : "Cold crystallization" is the exothermic phenomenon occurring during the heating process of a supercooled liquid. Molecules that exhibit cold crystallization can be used as heat storage materials. Schiff-base nickel(ii ) complexes containing a quaternary carbon bearing two methyl groups and alkyl chains of variable length (OC n -salmpn, where n = 2, 4, 6, 8, 10, 12, 14, 16, and 18) displayed complex thermal behavior, including cold crystallization. The steric bulk of the two methyl groups decreases crystallization rate, resulting in a supercooled state. The alkyl chains control both the thermal behavior and the aggregation structure, and the complexes are expected to be used as new heat storage materials. In addition to displaying complex thermal behavior, some OC n -salmpn complexes can incorporate chloroform molecules depending on the alkyl chain length, enabling additional functionality.